Deleterious effects of calcium indicators within cells; an inconvenient truth. (July 2018) - Bootman, Martin D.; Allman, Sarah; Rietdorf, Katja; Bultynck, Geert
Graphical abstract: Highlights: Ca 2+ signalling is widely studied using fluorescent indicators that can be readily loaded into living cells. Chemical Ca 2+ indicators can measure cellular Ca 2+ changes over long periods of time with sub-second resolution and microscopic precision. There are known problems with the use of chemical Ca 2+ indicators, which are largely overlooked. Genetically-encoded Ca 2+ indicators overcome some of the issues of using chemical Ca 2+ indicators, but may introduce problems of their own. Careful planning and control experiments may overcome the deleterious, off-target effects of chemical Ca 2+ indicators. Abstract: The study of cellular Ca 2+ signalling is indebted to Roger Tsien for the invention of fluorescent indicators that can be readily loaded into living cells and provide the means to measure cellular Ca 2+ changes over long periods of time with sub-second resolution and microscopic precision. However, a recent study [1 ] reminds us that as useful as these tools are they need to be employed with caution as there can be off-target effects. This article summarises these recent findings within the wider context of confounding issues that can be encountered when using chemical and genetically-encoded Ca 2+ indicators, and briefly discusses some approaches that may mitigate against misleading outcomes.